A keratin 15 containing stem cell population from the hair follicle contributes to squamous papilloma development in the mouse. Issue 10 (16th March 2012) - Li, Shulan; Park, Heuijoon; Trempus, Carol S.; Gordon, Derek; Liu, Yaping; Cotsarelis, George; Morris, Rebecca J.
<x xml:space="preserve">Abstract</x> The multistage model of nonmelanoma skin carcinogenesis has contributed significantly to our understanding of epithelial cancer in general. We used the Krt1‐15CrePR1;R26R transgenic mouse to determine the contribution of keratin 15+ cells from the hair follicle to skin tumor development by following the labeled progeny of the keratin 15 expressing cells into papillomas. We present three novel observations. First, we found that keratin 15 expressing cells contribute to most of the papillomas by 20 weeks of promotion. Second, in contrast to the transient behavior of labeled keratin 15‐derived progeny in skin wound healing, keratin 15 progeny persist in papillomas, and some malignancies for many months following transient induction of the reporter gene. Third, papillomas have surprising heterogeneity not only in their cellular composition, but also in their expression of the codon 61 signature Ha‐ras mutation with approximately 30% of keratin 15‐derived regions expressing the mutation. Together, these results demonstrate that keratin 15 expressing cells of the hair follicle contribute to cutaneous papillomas with long term persistence and a subset of which express the Ha‐ras signature mutation characteristic of initiated cells. © 2012 Wiley Periodicals, Inc.